Geochemistry of freshwater calcareous sediments and longevity impacts of their application to acidic soils of eastern Lithuania - Marcinkonis, Saulius; Karmaza, Bronislavas; Booth, Colin A. (Journal of Environmental Engineering and Landscape Management, 2012)
Numerous investigations on the quaternary depositions of natural calcareous sediments and their use for soil conditioning have been carried-out in the Baltic region. Locally sourced freshwater limestone were formerly introduced (1950s) for soil liming, due to the absence or limited availability of appropriate industrial materials. Nowadays, with a greater awareness and understanding of the CO2 issues surrounding the production of industrial lime (intensively heated during manufacture), together with increasing costs of its production and transport, attention has returned to previous approaches. The main aim of this study was the identification of geological distribution peculiarities of freshwater limestone depositions, spatial and vertical geochemical variation and modelling of their previous agricultural use in acid soils regions. Geochemical composition data of local lake limestone has been lacking in Lithuania. Studies reveal that the quality parameters of sediments mostly align with the minimum for standard lime requirements (EN ISO 12945:2008), but materials are geochemically diverse even between layers of the same deposit. Tests show calcareous materials are especially rich in total manganese (3500 ppm) and slightly lower was total barium concentrations (490 ppm). Just a few mg kg−1 less were total concentrations of silver, boron, cobalt, chromium, copper, gallium, nickel, lead and vanadium. Former use of these sediments for liming purposes with regard to the national hygiene norm (HN 60:2004) controlled elements disclaim direct risks of soil pollution by higher heavy metals and rare elements accumulation. Previous liming studies indicate natural limes offer slow acting degradability compared to industrial products (dust limestone) and longer lasting liming effect. However, heavy metals and rare elements applied to soils are locked in topsoil (diffusion is mainly limited to depth of soil tillage). Unfortunately, cessation of liming and accelerated soil acidification promotes increased element mobility, which raises the risk of higher accumulations in crops, and their transfer to the food chain and/or their transport to groundwater. Article in English. Geocheminė gėlavandenių kalkingųjų nuosėdų sudėties variacija ir jų naudojimo palikimas rūgštiems rytų lietuvos dirvožemiams Santrauka. Baltijos jūros regione atlikta nemažai tyrimų, kurių sudėtinė dalis – kalkingųjų kvartero nuosėdų tyrimai ir jų naudojimas dirvai gerinti. Gėlavandenės klintys buvo naudojamos dirvožemiams kalkinti trūkstant pramoninių kalkinių medžiagų. Šiuo metu jomis vėl domimasi, nes jos leidžia išvengti CO2 emisijų, susidarančių gaminant pramonines kalkines medžiagas (kaitinant klintis), jų naudojimas yra ekonomiškai patrauklus. Pagrindinis atliktų tyrimų tikslas – nustatyti geologinio paskirstymo ypatumus gėlavandenėse kalkingosiose nuosėdose, horizontalųjį bei vertikalųjį geocheminį pasiskirstymą ir ankstesnio šių medžiagų naudojimo žemės ūkio paskirties rūgščių dirvožemių regionuose išliekamąjį poveikį. Geocheminė gėlavandenių klinčių sudėtis anksčiau Lietuvoje nebuvo tirta. Atliekant tyrimus nustatyta, kad kalkingosios nuosėdos dažniausiai atitiko minimalių standartinių kalkinių medžiagų reikalavimų kokybės rodiklius (EN ISO 12945:2008), bet geocheminė šių medžiagų sudėtis yra labai įvairi net skirtinguose to paties klodo sluoksniuose. Buvo nustatyta, kad išanalizuotose kalkingosiose nuosėdose yra ypač daug suminio Mn (3500 ppm) ir šiek tiek mažesnė Ba koncentracija (490 ppm). Tik keli mg kg−1 ar mažiau buvo rasta suminių Ag, B, Co, Cr, Cu, Ga, Ni, Pb ir V. Modeliuojant buvusį šių nuosėdų naudojimą kalkinimo tikslais, vertinant pagal higienos normoje (HN) kontroliuojamų elementų koncentracijas, paneigtas tiesioginis dirvožemio taršos pavojus sunkiaisiais metalais ir retaisiais elementais. Šiomis medžiagomis kalkintuose dirvožemiuose sunkiųjų metalų ir retųjų elementų atsargos yra ilgam imobilizuotos (mobilesnės iš esmės yra tik armens sluoksnyje). Tačiau dėl nutrauktų kalkinimo darbų spartėjant dirvožemio rūgštėjimui, šių elementų mobilumas didėja, taip pat padidėja grėsmė susikaupti augaluose, patekti į mitybos grandinę ir užteršti gruntinius vandenis. Reikšminiai žodžiai: geochemija, horizontalioji ir vertikalioji variacija, dirvožemio kalkinimas, dirvožemio rūgštėjimas, higienos normos